2013
DOI: 10.1080/07315724.2013.767619
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods to Assess Reduced Body Fat in Patients with Anorexia Nervosa

Abstract: In our group of patients with AN, the Deurenberg skinfold model and DXA were similar in performance; however, DXA overestimated %BF in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Previously, Birmingham et al reported the inability of BIA to detect changes in body composition due to altered hydration, compared to skinfold measurements, in AN patients [9]. Skinfold measurements and DXA were similar in performance for the estimation of percentage of body fat in 80 AN patients [8]. Bonaccorsi et al compared BIA (BIA software and Deurenberg equations) to DXA in 30 young girls (11 to 19 years old) with AN [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, Birmingham et al reported the inability of BIA to detect changes in body composition due to altered hydration, compared to skinfold measurements, in AN patients [9]. Skinfold measurements and DXA were similar in performance for the estimation of percentage of body fat in 80 AN patients [8]. Bonaccorsi et al compared BIA (BIA software and Deurenberg equations) to DXA in 30 young girls (11 to 19 years old) with AN [6].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of body composition assessment by DXA and BIA in AN patients has been reported in some studies [6][7][8][9] showing inconsistent results. We previously reported in malnourished patients that BIA underestimated FFM and overestimated FM when using the manufacturer's BIA equation [10].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to exactly monitor the increase of body fat. For this purpose, skinfold anthropometry and DXA as well as whole-body impedance vector components, resistance (R) and reactance (X(c) have been used [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Elaborate methods such as dual-energy x-ray absorptiometry (DXA) as well as whole-body impedance vector components, resistance (R) and reactance (X(c) have been used in order to determine the body composition of AN patients [3][4][5][6]. Yet some investigators found that comparatively simple anthropometric measurements such as triceps skinfold thickness or girth at different regions of the body show a very good correlation to the elaborate measurements in AN, whereas BMI proved as less reliable [5,7].…”
mentioning
confidence: 99%
“…Deviations between predicted body fat based on quantitative surrogates (such as BMI) and actual body fat as measured by DXA are reported in studies of "atypical" groups such as muscular athletes, endurance athletes, jockeys, and individuals with eating disorders. [55][56][57][58][59][60][61][62][63][64][65][66][67]…”
Section: S45mentioning
confidence: 99%